ТHE RESEARCH OF THE SMALL MODULAR REACTORS USE IN UKRAINE - MALOHULKO, YULIIA; BANDURA, IRYNA; SLIDENKO, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
With the growth of the world population and the rapid development of the economy, the modern world is facing challenges related to energy security and sustainability. In this context, nuclear energy becomes an extremely important element of the modern energy system. Nuclear energy ensures the reliability of electricity supply, reduces dependence on coal and oil reserves and is one of the most environmentally safe forms of energy. Operating reactors have a maximum service life of 40-50 years, and SMRs will have almost 1.5 times longer service life, taking into account the fact that they will maneuver, and about 2 times more service time, if the number of power changes is minimized , that is, will be used only to replace the fuel, actually generate the base power. Safety is the main factor in the operation of such facilities. It is the highest priority in Ukraine, and only after confirming the safety of the technology are all other factors considered, including economic ones. Small modular reactors are safer, including due to passive safety systems. This means that even in the event of a nuclear winter, when a person will not be able to be present at the reactor control panel, will not be able to supervise and control the state of the power unit, the safety systems will independently, without human intervention, transfer the reactor to a safe state. Such safety systems reduce the risks of serious nuclear accidents A positive characteristic of SMRs is their smaller size compared to traditional reactors, this gives a lot of freedom when installing SMRs, in fact they can be placed in regions with limited access to build transit power lines to provide electricity to consumers and in the most remote regions, in fact create "energy islands" . As follows from general logic, the maximum capacity of SMR is 300 MW, and that of traditional reactors is 1100 MW, that is, three times less, and accordingly, the costs of building a separate SMRs will be lower. Although from an economic point of view, the cost of manufacturing SMRs per unit of installed capacity will be somewhat higher than that of traditional ones. This factor is offset by the fact that greater environmental safety will be achieved in the event of accidents, the tragic experience of which is already known to Ukraine and several countries in the world.
Keywords: small modular reactor; nuclear power plant; power regulation